Transcriptional Profiling of Resistant and Susceptible Cultivars of Grapevine (Vitis L.) Reveals Hypersensitive Responses to Plasmopara viticola - Gong, Peijie; Kang, Jun; Sadeghnezhad, Ehsan; Bao, Ruoxuan; Ge, Mengqing; Zhuge, Yaxian; Shangguan, Lingfei; Fang, Jinggui (Frontiers in Microbiology, 2022)
Grapevine downy mildew is the most serious disease of grapevine cultivars that affects the rate of resistance/susceptibility to Plasmopara viticola. In this study, we used the susceptible cultivar “Zitian Seedless” and the resistant cultivar “Kober 5BB” as materials to determine the transcriptome differences and phenotypes of the leaves after inoculation with downy mildew. The differences in microstructures and molecular levels were compared and analyzed. Fluorescence staining and microscopic observations confirmed that hypersensitive cell death occurred around the stomata in “Kober 5BB” infected by downy mildew zoospores. Meanwhile, transcriptomic profiling indicated that there were 11,713 and 6,997 gene expression differences between the resistant and susceptible cultivars at 72 h after inoculation when compared to control (0 h), respectively. The differentially expressed genes of the two cultivars are significantly enriched in different pathways, including response to plant-pathogen interaction, mitogen-activated protein kinase (MAPK) signaling pathway, plant hormone signal transduction, phenylpropanoid, and flavonoid biosynthesis. Furthermore, the results of functional enrichment analysis showed that H2O2 metabolism, cell death, reactive oxygen response, and carbohydrate metabolism are also involved in the defense response of “Kober 5BB,” wherein a total of 322 key genes have been identified. The protein interaction network showed that metacaspases (MCAs), vacuolar processing enzymes (VPEs), and Papain-like cysteine proteases (PLCPs) play an important role in the execution of hypersensitive responses (HR). In conclusion, we demonstrated that HR cell death is the key strategy in the process of grape defense against downy mildew, which may be mediated or activated by Caspase-like proteases.